An update on the diversity of marine sponges in the southern gulf of Mexico coral reefs - Ugalde, Diana; Fernandez, Julio C.c.; Gómez, Patricia; Lôbo-Hajdu, Gisele; Simões, Nuno (Zootaxa, 2021)
Until now, 127 species of marine sponges have been recorded in the southern Gulf of Mexico (SGoM). In this study, we describe the sponge fauna recorded on 16 coral reefs of the SGoM, defined as the Mexican waters of the Gulf of Mexico (GoM), during a period from 2005 to 2019. We report 80 sponge species, including 34 first geographic records for the southern GoM region. The latter are fully described and illustrated, taking into account 24 that represent new records for the GoM: Agelas conifera, Agelas sventres, Agelas wiedenmayeri, Prosuberites carriebowensis, Desmanthus meandroides, Cliona aprica, Cliona dioryssa, Placospongia ruetzleri, Haliclona (Gellius) megasclera, Haliclona (Reniera) aff. portroyalensis, Neopetrosia proxima, Xestospongia arenosa, Calyx podatypa, Shiphonodictyon xamaycaense, Acarnus innominatus, Iotrochota arenosa, Polymastia tenax, Svenzea cristinae, Svenzea flava, Svenzea tubulosa, Svenzea zeai, Timea stenosclera, Stellettinopsis megastylifera, Suberea flavolivescens. The present work highlights the understimated and remarkable diversity of reef-associated sponges within the Campeche Bank Coral reef systems. Present work data was compiled with existing published information to produce an updated list of 161 known sponges in the southern GoM.